Strategies Affecting the Decision for Vaccination among Parents of Children Aged 0–3-Years Old who Hesitate and Refuse to Vaccines: A Phenomenological Study in the Southern Border Provinces - Somkird, Jinjuta; Sawan, Sarinee; Jeharsae, Rohani; Nimu, Nisuraida; Talek, Muhamadfahmee (Princess of Naradhiwas University Journal, 2025)
Background and objective Coverage of national immunization program for children age 0-3 years old in the deepsouth of Thailand has been low for many years. Even though there are several programs have been implemented to solve this situation, the coverage rate has not improved. This phenomenological study aims to describe strategies affecting the decision for routine immunization among parents of 0-3 years children living in southern border provinces who hesitated or refused against vaccines. Methods Focus group discussions were held with 3 groups of participants including 1) children’s parents 2) health workers and 3) health volunteers, community and religious leaders with a total of 158 participants from 6 communities in Pattani, Yala and Narathiwat. Study communities were recruited purposively based on the recommendations of the provincial health offices. Participants were selected purposively align its inclusion criteria of selection. Focus groups discussions were held around 90-120 minutes for each group approximately with audio tape recording and concept mapping. At the end of focus group discussions, researchers presented concept mapping to participants for content validation. Verbatim transcription was performed, the Colaizzi’s qualitative analysis method for phenomenological study was applied, trustworthiness was done by a total of 59 participants and experts. Results Results showed that there were 4 strategies including 1) imposing conditions 2) positive reinforcement 3) humanized care and 4) customer focused services were influencing to parent’s decision on routine immunization for their children. Imposing conditions and providing incentives had rapidly driven parents’ decision to immunize their children but these two strategies were not sustainable in the long term. In the other hands, humanized care and customer focused strategies were slowly affected to parent’s decision for immunization their children but it seemed to be long term sustainable. Summary and recommendation Imposing conditions, positive reinforcement, humanized care and customer focused services are the effective strategies for improving vaccine coverage in the deep south of Thailand. Various strategies are needed for encouraging children’s parents to decide for immunization their children.